Analisis Konsumsi Energi Listrik dan Bahan Bakar KMP. XYZ dalam Mendukung Operasi Pelayaran di Nusa Tenggara Timur - I Made Aditya Nugraha; Febi Luthfiani; Grangsang Sotyaramadhani; Muhamad Amril Idrus (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The generation and use of good electrical energy on a commercial ship will provide a sense of comfort and safety for everyone who uses the facility. The XYZ ship is one of the commercial ships in East Nusa Tenggara which operates to serve crossings from Kupang to Rote. This ship uses 3 generators to meet its electrical energy needs. This study aims to determine the consumption of energy and fuel used during shipping activities and to determine the condition of the generator used. The results of the analysis show that the percentage of generator loading on the ship's electrical load is still sufficient, with an average of 8.76%. The fuel consumption of the generator in one operation is 200.34 Liters/day, which is still appropriate and sufficient for the capacity of the fuel chamber on the ship. The use of generators is also carried out effectively and efficiently with alternating scheduling so that each generator can work optimally for a long time to avoid overheating.